Akibat Hukum Terhadap Limbah Sampah Plastik Di Teluk Ambon Berdasarkan Undang-Undang Nomor 18 Tahun 2008 Tentang Pengelolaan Sampah - Abnu Fauzi Mesfer; La Ode Angga; Sabri Fataruba (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Public awareness in disposing of waste, often causes them not to waste space, such as throwing garbage in ditches, rivers, and even in the ocean. Purposes of the Research: To find out and analyze forms of plastic waste management in Ambon Bay based on Law Number 18 of 2008 concerning Waste Management, and as a requirement for obtaining a Bachelor of Law degree at the Faculty of Law, Pattimura University, Ambon.Methods of the Research: This research is a type of normative legal research, namely legal research whose object of study includes the provisions of legislation and legal materials of a documentary nature, with the main subject of the study of the problem of Danpak implementation of reclamation in Ambon Baguala bay.Results of the Research: Forms of plastic waste management in Ambon bay based on Law Number 18 of 2008 concerning Waste Management, namely: the forms of waste processing in Ambon city initially from TPA-TPA to an open dumping system to a better system in accordance with Law Number 18 of 2008 concerning Waste Management, through four choices of waste processing scenarios.